HUBUNGAN MINAT BACA DAN MOTIVASI BELAJAR DENGAN KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 24 PADANG - Ria Satini; Atmazaki .; Abdurahman . (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: This study aims to explain the following. First, the relationship with the reading skills of news writing students class VIII SMP Negeri 24 Padang. Secondly, the relationship between motivation to learn the skills of news writing students class VIII SMP Negeri 24 Padang. Third, the relationship of reading interest and motivation to learn the skills of news writing students classVIII SMP Negeri 24 Padang. The population was classVIII SMP Negeri 24 Padang. Sampling are 40 student performed using proportional random sampling technique. Data collected through questionnaires and performance tests. Questionnaire used to see interest in reading and students' motivation, while performance tests conducted to determine the outcome of news writing skills of students. Analysis and discussion of the data is done in accordance with the concept of descriptive correlational study. Based on the research conducted can be summarized as the following three things. First, there is a significant correlation between interest in reading the news writing skills students class VIII SMP Negeri 24 Padang. Secondly, there is a significant relationship between motivation to learn the skills of news writing students class VIII SMP Negeri 24 Padang. Third, there is a significant relationship between interest in reading and learning motivation together with news writing skills students class VIII SMP Negeri 24 Padang. Keywords: reading, learning motivation, news writing skills